Conflict Management in Protected Areas - Srivastava, Sanjay (Indian Forester, 2000)
Wildlife Management in India suffers from a variety of problems - governmental neglect, insufficient financial resources, a lack of conservation education and poor or non-existent regulatory structures. The conflicts resulting from these problems relate to the lack of process of involving local people in the planning, management and decision making for the area, that conflict with the very objectives of the Protected Area. There may be certain general principles applicable to the majority of Protected Area conflicts in the form of evaluation of underlying interests and involvement of significantly affected stakeholders in a fair and respectful process while trying to resolve a conflict. Providing benefits to local people and mitigating the adverse impacts of the Protected Area along with enforcement and conservation education are the keys to addressing conflicts in many situations. To ensure successful long-term management, the development of a relationship based on trust and cooperation between the key Protected Area stakeholders is critical.